Virtue in Farming: Study of Takhrij and Syarah Hadith on Agrotechnology - Titian Lismaya; Kifah Gibraltar Bey Fananie; Tuti Garnasih; Cermi City Mulyanti (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the hadith of primacy in farming. These research methods are qualitative through the approach of earldom and hadith. The results and discussions of this study are that farming is a noble work favored by god almighty. Farming has many benefits to its neighbors. The conclusion of this study is the throne and the prophet syarah hadith concerning priority in farming that is counted as charity for muslims who grow plants and then benefit humans, animals or other living creatures.